Praktek Predatory Pricing dalam Perspektif Maqashid Syariah - Faishol, Muhammad; Nisak, Luluk Nur Sayidatin; Najib, M. Thoha Ainun; Mukminin, mas Ach Azmi; Sadid, M. Ashilus (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2022)
Export and import activities cannot be denied by a country in order to meet the needs of its people, as well as a means of development, especially to increase the export aspect of state products. Competition is something that cannot be avoided from every country in seizing international market share and even world market share. Competition is not only carried out in a healthy manner, sometimes even in an unhealthy way, such as selling products at prices above the market price in general, even selling below a fair price with the aim of seizing market share and causing damage to market mechanisms, one of which is by conducting predatory pricing practices price. This unhealthy practice makes MSME actors and domestic industries feel disadvantaged, it will even have a negative impact on the economy of a country. This study is to see predatory pricing practices in the eyes of maqahid sharia using the pheno approach which is currently being sought after by MSME activists. The method used is descriptive analysis as an effort to solve problems by describing and explaining predatory pricing and its relationship with sharia maqashid. In the view of Islamic economics, the term predatory pricing is known as إغراق (ighraq), and Islam forbids ighraq because it is a trade practice that contains harm.